Zwischen fragwürdiger Historiosophie und utopischen Entwicklungsperspektiven: Das weltanschauliche Angebot der beiden ersten Romane von Johannes Mario Simmel - Bialik, Włodzimierz (Wydawnictwo Naukowe UAM, 1990)
In the article the author writes about two novels „Mich wundert, daß ich so fröhlich bin“ (1948) and „Das geheime Brot“ (1950). The problematic historiosophic conceptions which were at the basis of the first of the two novels by Simmel, and which pointed one time to the unmasking of the (false) historical consciousness of German society by the author, and another time to the unmasking of his (the author's) own problematic historical consciousness. These conceptions were "replaced" in the second novel additionally by the “utopian naive” conceptions of the further historical development of Germany. Early novels of Simmel are an evidence of world-view convulsions of the German society in the first post-war years and of helplessness of the author himself as far as the world-view.